A new minute pirate bug of the genus Scoloposcelis (Hemiptera: Heteroptera: Anthocoridae) from West Malaysia - Yamada, Kazutaka (Zootaxa, 2014)
Scoloposcelis seidaii sp. nov. is described from the Malay Peninsula based on a single specimen collected under the bark of a decaying tree. This discovery represents the first distribution record of the genus Scoloposcelis from Malaysia. Habitus photographs and diagnosis of S. parallela (Motschulsky, 1863) are provided for comparison with S. seidaii.